2020
DOI: 10.1177/0734242x20918013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pond ash-bentonite mixes as landfill liner material

Abstract: Characterization of pond ash-bentonite mixes is made to assess their suitability as liner material for waste disposal facilities by examining the relevant index and engineering properties. Further, a comparative assessment is made between sand-bentonite and pond ash-bentonite mixes for the range of bentonite content varying from 0 to 30% by weight at an interval of 5% to ensure an effective substitution of sand with pond ash. Addition of bentonite to sand or pond ash significantly influences the plasticity, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Soil structure is a unique and important feature governing the development of plants, absorption of nutrients, growth of roots [ 1 ], aeration and water transport [ 2 ], resistance to erosion [ 3 ], and many others features. The strength and durability of soil structure are key factors influencing a number of soil performance characteristics, such as stability of landfill liners, specific barriers for nuclear waste disposal, foundations for buildings, roads and embankments [ 4 , 5 , 6 , 7 ], soil bearing capacity [ 8 , 9 ], settlement [ 10 ], deformation by machines [ 11 ], the velocity of seismic waves [ 12 ] and many others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil structure is a unique and important feature governing the development of plants, absorption of nutrients, growth of roots [ 1 ], aeration and water transport [ 2 ], resistance to erosion [ 3 ], and many others features. The strength and durability of soil structure are key factors influencing a number of soil performance characteristics, such as stability of landfill liners, specific barriers for nuclear waste disposal, foundations for buildings, roads and embankments [ 4 , 5 , 6 , 7 ], soil bearing capacity [ 8 , 9 ], settlement [ 10 ], deformation by machines [ 11 ], the velocity of seismic waves [ 12 ] and many others.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of multicomponent systems of clay minerals, Ye et al [ 25 ] showed that montmorillonite significantly increased the compression of kaolinite-based clayey soils, while contents of illite and chlorite were less influential in these systems. The beneficial effect of bentonite on the hydraulic conductivity, mechanical stability and permeability were indicated in mixtures with sand, pond ash or fly ash [ 5 , 6 , 26 ]. Charkley et al [ 27 ] reported an increase in cohesion and shear strength with an increase in kaolinite/montmorillonite content in artificial clay soil.…”
Section: Introductionmentioning
confidence: 99%